DAMPAK KEBERADAAN ALFAMART DAN INDOMARET TERHADAP WARUNG KECIL DIKELURAHAN SIMPANG BARU KOTA PEKANBARU - Ahmad Dul Hadi Hutabarat; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The aim of this study was to determine the impact of the existence of Alfamart and Indmaret on small stalls in Simpang Baru Village, Pekanbaru City. This type of research is descriptive quantitative. The population in this study are small shops that are close to Alfamart and Indomaret. The research results explain that the factor that greatly influences the impact of Alfamart and Indomaret is the distance to small shops, where the farther the distance between Alfamart and Indomaret, the more income generated by small shops. In contrast to the small stalls that are located close to Indomaret and Alfamart, the income generated is less. Keywords: Factor, Distance, Income